Unilateral Fusion Of Teeth In Mandibular Arch - An Unusual Finding - Banerjee Abhishek; Rashmi M; Baruah Akash Narayan; Chugh Niranjan Kumar; Pranay Dutta Dwivedi (ziauddin University, 2022)
Fusion of two teeth is rare developmental disorder which is encountered by a clinician. It is commonly reported in deciduous dentition. The fused crown appears broader and usually an esthetic concern. This condition usually reveals a decreased teeth count. Unilateral occurrence of fusion in permanent mandibular anterior teeth is a rare phenomenon. Hence this case report is presented.